Do innovation and internationalisation policies improve regional performance? - Mariasole Bannò; Celeste Amorim Varum; Valentina Morandi (European Regional Science Association (ERSA), 2011)
This paper investigates empirically determinants of regional growth. The scant literature that exists indicates that a region's economic growth depends to a large extent on several features of the regions themselves, which evolve slowly over time. Our results contribute to this set of literature, accounting also for policy variables, which have been by far neglected. Indeed, due to numerous market failures, measures to promote innovation and internationalization have been prominent in government policies in the last decade. This follows because, there is a consensus among academics, policy makers and practitioners that innovation and internationalization has become increasingly important for the growth of regions and countries. The effect of such ad hoc policy measures by home governments to promote innovation and internationalization has scarcely been studied, and existing studies addressing this issue have mainly a national focus. Despite the clear theoretical justification for the public support, policy makers ask for robust empirical evidence on these matters. This paper contributes to this end. The novelty of the study is in the emphasis on the impact of public policy tools (for innovation and internationalization), and on the coordination between them, upon regional growth. The study is conducted for the 20 Italian regions over the period 1998 to 2008. It tests not only the importance of regional characteristics but also the effects of public policy measures upon the regional economic growth. We focus in specific in the role of innovation and internationalization policy related measures. The results reveal the importance of regional characteristics and also of policy measures. The empirical findings are in line with the theoretical hypotheses: public incentives are key for promoting growth, and they have to be seen in the broader context of the determinants of regional growth. The paper also derives conclusions regarding the interrelationship between policies for innovation and for internationalization. Moreover, the allocation of incentives does not seem to help counterbalance the regional asymmetry, and the global processes and challenges are likely to strengthen the gap between regions.
Keywords: 330